ASAS KEPASTIAN HUKUM, KEADILAN DAN KEMANFAATAN DALAM KAITANNYA DENGAN PUTUSAN KEPAILITAN PENGADILAN NIAGA - Tata Wijayanta (Jurnal Dinamika Hukum, 2014)
The principles of legal assurance, justice and expediency are properly stipulated in the provisions of the Act Number 37 Year 2004.  The legal assurance is seen by the rapidity of the settlement and the expeditious evidentiary procedure. The justice is reflected in equality principle in the proceeding. Then, the expediency is conceived from the imposition of bankruptcy as the last resort (ultimum remidium ) and the application of open to public-trial. Nevertheless, in certain case laws from the Commercial Court, the principles were not applied harmoniously.  The legal assurance appears to be more emphasized than the other principles. Take for example the bankruptcy case of PT Telekomu-nikasi Phones (District-Commercial Court of Central Jakarta Number: 48/Bankruptcy/2012/PN Nia-ga.Jkt.Pst) that has been reviewed and nullified by the Supreme Court Number: 704K/Pdt.Sus/ 2012).Key words:  legal certainty, justice, expediency, bankruptcy decision.